Understanding Fiqh Material Through The Study Book of Fathul Qorib - Muhammad Fodhil; Farhan Dwi Fathurrozi (LPPM Universitas KH. A. Wahab Hasbullah, 2021)
This article examines the learning method the book of fathul qorib as a step to improve understanding fiqh material in learning, so that students can understand, interpret, conclude, explain and solve a problem. This article study uses a qualitative method through case studies. The results of this study are the learning process using several classical methods as a support in increasing students' understanding including the tahasus method, the syawir/discussion method, the sorogan method and the bandungan method. As for additional activities to deepen understanding, ubudiyah practice activities and munakahat practices are carried out in each dormitory called jam'iyah activities. Thus, students are able to read, translate and explain fiqh material with different abilities. Through this method, it is expected that students can achieve maximum results in accordance with the planned learning objectives.